THE FORMATIVE EFFECTS OF GRAPHIC ORGANIZERS IN ACHIEVING SITUATIONAL LEARNING - Florentina MOGONEA; Florentin Remus MOGONEA (Universitaria Publishing House, Craiova, 2024)
Situational learning is one of the teaching options that can ensure the efficiency of the activity, as it allows capitalizing on students' previous experience and provides a link between new content elements and examples in the immediate reality. The appeal to different graphic organizers in carrying out situational learning increases the effectiveness of this approach. This study analyzes the formative effects of graphic organizers in achieving situational learning. The research undertaken was based on the use of two research methods: questionnaire-based survey and focus-group interview. The opinion questionnaire was applied to a sample of 58 master students, in the first year, at the Faculty of Letters, University of Craiova, and who are, at the same time, enrolled in the initial training program as teachers, and the interview was conducted with 10 students from the same faculty. The results obtained from the application of the two research tools allowed the identification of teachers' training needs regarding the conditions of methodological efficiency of capitalizing on situational learning in practice, facilitated by different graphic organizers. Based on the results obtained, we propose the use of tools to optimize the process of training and developing the competences of a future teacher. Some of these tools have been developed and harnessed in previous research and improved, but there are also new proposals.